Implementation and performance evaluation of an integrated specimen referral system in Burkina Faso using the national courier services (2020–2022) - Dama, Emilie; Porgho, Souleymane; Ake, Yahn-Cedric; Yameogo, Issaka; Gampini, Sandrine; Adjami, Aime-Gilles A.; Nikiema, Abdoulaye; Kamate, Mory; Tarbangdo, Felix; Sawadogo, Romial; Sawadogo, Charles; Ouedraogo, Hamed S.; et al. (Frontiers in Public Health, 2024)
Introduction In 2017, the Ministry of Health and Public Hygiene (MoH) of Burkina Faso designed and piloted a specimen transport system using the national courier services (La Poste BF) in 4 districts. Based on satisfactory performance indicators, the MoH set a vision aimed at scaling up this system to strengthen disease detection and surveillance of epidemic prone diseases across the country. This work describes the implementation process, performances, and lessons learned. Methodology This work describes the implementation process, performances, and lessons learned. Under the leadership of the Directorate of Population Health Protection within the MoH, a stepwise approach was used to bring together multiple partners across sectors to develop the first needed documents including a guide, an implementation plan, Standard Operating Procedures, and data collection tools. Then, the execution phase included equipment purchase, trainings, and consensus on a financing mechanism. Key indicators were defined to allow performance monitoring Result The integrated biological specimen referral system (SITEB) was officially launched in January 2020 to transport human biological specimens of priority diseases including COVID-19 from district level to reference laboratories nationwide. As of December 31, 2022, La Poste BF transported 168,856 packages containing 206,314 specimens from all 13 regions. 99.66% of packages were delivered in <24 h as required, and 99.68% of specimens were in good condition at reception. COVID-19 specimens represented respectively 18% and 63% of samples transported in 2020 and 2021. Discussion The political will combined with the experience gained during the pilot phase and the commitment and support from all stakeholders laid to the foundation of the effective implementation of this system. Collaboration between two government entities (MoH and Minister of Transport, Urban Mobility, and Road Safety) to benefit public health has led to reasonable pricing for sustainability. Although all documents integrate the “One Health“ approach, the system ensures the transport of only human samples for now. Despite security constraints, Burkina Faso has successfully set up a system using the national postal service to ensure the routine transport of specimens for all diseases under laboratory surveillance including laboratory tests for HIV and TB from the district level to reference laboratories nationwide. This system has also proved to be useful and efficient in managing public health emergency.